2007
DOI: 10.1002/j.2055-2335.2007.tb00663.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Management of Pain in Older People

Abstract: The prevalence of pain increases with advancing age. Pain is often undiagnosed or under-treated in older patients, particularly those with cognitive impairment, communication problems or residents of aged-care facilities. The most definitive approach to the management of pain is to treat the underlying cause. As this is often not feasible in the elderly, the emphasis then shifts to symptom control. Pharmacological approaches form the mainstay of therapy. They are convenient and often cost-effective, and may be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Assessment of pain in older adults with dementia and communication disorders is especially challenging; this topic is addressed in greater detail below. It has been suggested that effective pain management in elderly patients should include both pharmacologic and nonpharmacologic strategies (Ersek et al 2003, Katz 2007. Pharmacologic strategies call for administration of nonopioid analgesics, opioid analgesics, and adjuvant medication.…”
Section: Age-related Issuesmentioning
confidence: 99%
“…Assessment of pain in older adults with dementia and communication disorders is especially challenging; this topic is addressed in greater detail below. It has been suggested that effective pain management in elderly patients should include both pharmacologic and nonpharmacologic strategies (Ersek et al 2003, Katz 2007. Pharmacologic strategies call for administration of nonopioid analgesics, opioid analgesics, and adjuvant medication.…”
Section: Age-related Issuesmentioning
confidence: 99%
“…All medications must be considered carefully and balanced with regard to risks and benefits for each individual. 'Rational polypharmacy' refers to the concept of using combinations of analgesics with different modes of activity which may be more effective than when used alone and lead to a reduced side effect profile: for example, paracetamol and sustained release oxycodone for moderately severe musculoskeletal pain [42].…”
Section: Pharmacological Therapiesmentioning
confidence: 99%
“…Attempting to achieve total eradication of pain is likely to lead to intolerable side effects. Patient and carer education is vital to assist in setting realistic goals of therapy [42].…”
Section: General Principlesmentioning
confidence: 99%
“…Pain management was reviewed again in 2007 and 2016. In 2007 the cardiovascular risks associated with NSAIDs were noted for the first time, and in the 2016 review it was stated that regular use of NSAIDs is generally not recommended in older people . Reflecting increased awareness of their risks, and availability of a wider range of analgesic options, NSAID usage has fallen over the last 10 years …”
Section: Early Articles and Changes In Therapeutics Over The Last 30 mentioning
confidence: 99%
“…In 1998 neuropathic pain was briefly addressed, and carbamazepine, valproate, phenytoin, mexiletene and TCAs were suggested drug therapies . In 2007, gabapentin, pregabalin and lamotrigine were preferred options, with TCAs as a second‐line option . By 2016 additional options were available, including the serotonin‐noradrenaline reuptake inhibitors (e.g.…”
Section: Early Articles and Changes In Therapeutics Over The Last 30 mentioning
confidence: 99%